Spontaneous magnetostriction in the Gd-Y system: analysis of phase transformations - Beznosov, A.B.; Fertman, E.L.; Eremenko, V.V.; Pal-Val, P.P.; Popov, V.P.; Chebotayev, N.N. (Физика низких температур, 2001)
The transformations of magnetic and lattice subsystems states of Gd₁₀₀₋xYx (x=0, 5.5, 7.5, 10.2) alloys have been studied at temperatures 5-370 K in magnetic fields up to 4 kOe. The temperature dependences of elastic modules, thermal expansion, low field magnetization and magnetic anisotropy parameters were obtained. The linear spontaneous striction ΔL(T)/L=xh² was analized, and the effective order parameters η and magnetostrictive parameters ξ were evaluated for the four magnetic phases (canted ferromagnetic, deforming ferromagnetic helix, ferromagnetic helix, and the ferromagnetic cone, respectively): ξcf=2.2×10⁻⁵, ξdh=- 5.3×10⁻⁵, ξfh=7.1×10⁻⁵, ξfc=1.4×10⁻³.